Assessment of patient safety culture in Brazilian hospitals through HSOPSC: a scoping review - Marcela Moreira Nascimento Prieto; Renata Elizabete Pagotti da Fonseca; Silvia Helena Zem-Mascarenhas (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to describe, from literature, the characteristics of patient safety culture in Brazilian hospitals that applied the Hospital Survey on Patient Safety Culture. Methods: this is a scoping review. A search was performed in the databases LILACS, PubMed, SciELO, CINAHL, Web of Science, Scopus and in the CAPES Dissertations and Theses Database in September and October 2020. Results: thirty-six studies were identified. Nine studies identified strengthened areas such as: "teamwork within the units", "expectations of supervisor/boss and actions promoting safety", "organizational learning", "support of hospital management for patient safety" and "frequency of report of events". As a critical area, the dimension "non-punitive response to error" was evidenced in 30 of 36 studies. Conclusions: the identification of areas of strength and critical areas of safety culture is relevant to encourage improvement of patient safety problems in an institution.